2022
DOI: 10.2147/idr.s353688
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Clearance of Viral RNA in Sputum for Severity COVID-19 Patients with Initial High Viral Load

Abstract: Aim To analyze the possible risk factors of delayed virus clearance in hospitalized patients with coronavirus disease 2019 (COVID-19). Methods Retrospective analysis of patients with COVID-19 admitted to the isolation wards from our hospital from 19th Jan 2020 to 18th March 2020. We were collected patient’s data including demographic, epidemiologic, and clinical information, as well as laboratory and radiologic findings. The possible confounding risk factors for prolong… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 19 publications
(23 reference statements)
1
8
0
Order By: Relevance
“…The Ct values of RT-PCR tests for SARS-CoV-2 are the most acknowledged and convenient indicator for viral load in COVID-19 patients at present [27,28]. The low Ct values were shown to be associated with delayed clearance of viral RNA in patients infected with previous SARS-CoV-2 variants [8,9], and our findings further supported that it could be the same case in Omicron-infected patients. A recent study showed that the symptomatic COVID-19 cases across each variant, including Omicron, had higher viral loads than the asymptomatic cases [22].…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…The Ct values of RT-PCR tests for SARS-CoV-2 are the most acknowledged and convenient indicator for viral load in COVID-19 patients at present [27,28]. The low Ct values were shown to be associated with delayed clearance of viral RNA in patients infected with previous SARS-CoV-2 variants [8,9], and our findings further supported that it could be the same case in Omicron-infected patients. A recent study showed that the symptomatic COVID-19 cases across each variant, including Omicron, had higher viral loads than the asymptomatic cases [22].…”
Section: Discussionsupporting
confidence: 78%
“…A few studies on COVID-19 patients during the Omicron wave showed that their median length of hospital stay (LOS) was 3-3.2 days [4,5]. Meanwhile, age, more severe clinical symptoms, non-vaccination, comorbidities, and low cycle threshold (Ct) values of the RT-PCR tests were shown to be associated with prolonged viral clearance and LOS in patients infected with previous variants [6][7][8][9][10]. Since Omicron is the dominant disease-causing variant at present and the majority of Omicron-infected COVID-19 patients were reported to be asymptomatic and mild cases [11][12][13][14][15], this study aims to demonstrate the clinical characteristics and LOS in a cohort of asymptomatic and mild COVID-19 patients during the wave of the Omicron epidemic in Shanghai from the largest municipal-level makeshift hospital with a capacity of 50,000 beds, the National Exhibition and Convention Center (NECC) Makeshift Hospital, and to investigate the risk factors for the prolonged LOS due to prolonged duration of viral shedding.…”
mentioning
confidence: 99%
“…The median duration of viral shedding of these prolong RNA positive patients was 16 days (IQR, 15-18 days), while seven (6-8) in control group. The median duration of these prolonged RNA positive patients testing negative first was 3 days (IQR, 3-5 days), while eight (5)(6)(7)(8)(9)(10)(11) in control group (Table 1…”
Section: Clinical Characteristics Of Patients In This Studymentioning
confidence: 99%
“…They found that delayed admission to hospital, male, and invasive mechanical ventilation were independent factors associated with the duration of SARS-CoV-2 RNA shedding. Zhao et al ( 9 ) retrospectively analyzed 104 patients with COVID-19 admitted to the isolation wards of our hospital from January 19 to March 18, 2020. The result showed that the clearance of viral RNA in sputum was delayed in severe COVID-19 patients, especially in those with a lower virus cycle threshold (Ct) value.…”
Section: Introductionmentioning
confidence: 99%
“…Omicron COVID-19 variant-infected individuals were identified using a reverse transcription PCR and the subsequent genomic sequencing. Asymptomatic, mild, moderate, severe, and critically ill patients were defined as previously described ( 7 9 ). Subjects who received other types of vaccines were excluded.…”
Section: Methodsmentioning
confidence: 99%